UJI KELAYAKAN AHLI MATERI PADA PENGEMBANGAN MEDIA PERMAINAN TRADISIONAL ENGKLEK DIKONSEP GEOMETRI ANAK USIA DINI - Istiqomah, Nurul; Sandra E, Ifa Aristia (Thufuli, 2020)
This research and development aims to determine the feasibility level of the material in the traditional early childhood crank game media. The media development method used in this development was adapted from the Thiagarajan 4-D development model. Data collection techniques from the results of a questionnaire or questionnaire. The results of the validation carried out by two material experts are as follows: 1) Conformity with Basic Competence (KD) is 4 with 80% eligibility criteria. 2) Learning aspect is 3.6 with 72% eligibility criteria. 3) Material presentation is 4 with 80% eligibility. So it can be concluded that the material on the traditional crank game media "WORTH" to be presented.